The School of Salamanca in the Affairs of the Indies - Matsumori, Natsuko. (Florence)
1 online resource (290 pages)
Keywords: The School of Salamanca in the Affairs of the Indies explores the significance of Salamancans, such as Vitoria and Soto, and related thinkers, such as Las Casas and Sepúlveda, in the formation of the early modern political order. It also analyses early modern understandings of political order, with a focus both on the decline of the medieval universal world through the independence and secularization of political community and the establishment of continuous and imbalanced relations between various European and non-European political communities. Through its investigation, this book highlights how Salamancans and related thinkers clearly distinguished their understandings of political order from medieval thought, and did so in a different way to contemporary and later thinkers, such as Machiavelli, Luther, Bodin, and Grotius, particularly with regards to the Indies, "barbarian" worlds. It also reveals the strong contribution of the School of Salamanca in early modern political thought, both internally and externally. Salamancans imposed moral restrictions against "interior barbarism," that is, power beyond law, and included "exterior barbarism," that is, "barbarian" societies, in the common political order. Situating the School of Salamanca in the mainstream history of European political thought, The School of Salamanca in the Affairs of the Indies is ideal for academics and postgraduate students of intellectual history and of Spanish colonial expansion.